Answer:
r = 7
Step-by-step explanation:
60 = -24 + 12r
<u>+24 +24</u>
84 = 12r
84 ÷ 12 = r
7 = r
Check:
60 = -24 + 12r
-24 + 12(7)
-24 + 84 = 60
Answer:
Associative property of addition. Grouping different addends does not change the sum.
Step-by-step explanation:
5 + 2 + 3 = 5 + (2 + 3)
10 = 5 + (5)
10 = 10
The answer to this is (4,0)
Answer:
B
Step-by-step explanation:
B. 48
9/12 must equal the x/64. 64/12 is 5.33333 repeating so multiply 9 x 5.33333 repeating would equal to 48
Answer:
C = -10x+3
Step-by-step explanation:
So the simplified version of the main expression is -10x+3. after finding the main expression you just need to simplify the rest of them too.
A. = -10x+9
B. = 8x-9
C. = -10x+3
D. = -10x-3
Now that you simplified all the expressions, you can pick out the one that's the same as the target expression, which is C.